Four Generations For Generations: A Pow Wow Story to Transform Academic Evaluation Criteria - Absolon, Kathleen (Engaged Scholar Journal, 2021)
Within this article, I share a story of four generations of my family and community coming together through pow wow dancing. I present the storying and re-storing of Indigenous scholarly engagement through pow wow regalia making and dance to accomplish two things: 1) to center Indigenous knowledge, kinship and community work through scholarship; and 2) to generate merit and value in the good work in which Indigenous scholars engage. Our creative and cultural selves are often excluded in terms of what receives value and merit in collective agreements. The academy wants us to teach, publish, and engage in community service. My community service is often within Indigenous kinship and community service where I engage in creativity and expressive arts. Evaluations of our tenure attribute value, credit, and merit for work produced, service generated, and research conducted steeped in a eurowestern definition of scholarly work. We theorize about the significance and importance of our culture and traditions; however, our families and communities’ practices are regarded as external and outside of the eurowestern academic contexts. This article brings together the knowledge of preparing for and dancing in a pow wow as valued and good work of Indigenous scholars within the academy. It calls attention to a need to revise systems of value and merit in a manner that benefits Indigenous scholars’ whole knowledge systems.